Modelling of smart intelligent materials with PZT & PVDF sensors/actuators to control the active vibrations of flexible aluminum mechanical cantilever beams using proportional integral derivative (PID) techniques. (2021) - Kusagur, Satvik M.; Arunkumar, G.; Manjunath, T.C.
Abstract: Modelling of smart intelligent materials with PZT & PVDF sensors / actuators to control the active vibrations of flexible aluminum mechanical cantilever beams using PID techniques is presented in this research article. A multi input multi output beam (flexible cantilever beam) is considered as the single point of attraction and this is the plant, which is to be subjected to the vibrations, this could be treated as the wing of an aircraft attached to the hub. The flexible mechanical aluminium cantilever beam is subjected to vibrations, say an external force being acted upon by the wind pressure or an exciter. Smart materials have got some special properties that react to the changes in their environmental conditions. The beam is subjected to vibrations. These vibrations should be suppressed in no time, else, the plant may get damaged. Hence, we put piezoelectric (PZT) and poly vinyl derylene fluoride (PVDF) sensor and actuators at 2 different positions to sense the vibrations and act upon immediately to neutralize it. The PZT sensors sense the vibrations & the actuators give an actuating signal to the controller, which in turn generates anti signals to neutralize the effect of the primary source of vibration. We have used the multi-sensor data fusion concept as if we use the same sensor and actuator, we may not get good results. Mathematical modelling of sensor and actuators of the 2 types is done, this is used to design the PID controller to suppress the vibrations in no time. The paper shows the effect of the multi sensor actuator pair of smart intelligent materials used in the vibration suppression. The work done can also compared with others to show the authenticity or the profoundness of the methodology proposed with the help of materials used in the theory of material science.